Integralność człowieka w świetle jego statusu rodzinnego - Smyczyński, Tadeusz (Wydział Prawa i Administracji UAM, 1988)
The problem of human integrity appears in the context of international documents concerning the protection of human rights. In the author's opinion, there are no grounds to formulate a separate right to integrity. Human integrity should be conceived as a directive of interpretation necessary to assess and implement all human rights. However, integrity should be perceived as referring not only to a human being as a separate individual, but as a member of a family group he himself established or belongs to. Life of an individual is connected with a family, which constitutes natural environment of human existence. Belonging to a family apparently limits integrity of an individual in the sense of his/her autonomy correlated with the lot and well-being of other members of the family. At the same time, however, one may notice that the participation in a family „enlarges" one's personality and thus his/her integrity is also enlarged by those elements which are common for all family members, e.g. dignity, good fame, privacy of family life, etc. Family thus appears as a specific point of reference in an integral approach to the protection of an individual.
Human integrity in the light of family status of a person